PENERAPAN REVERSE MECHANISM SELECTION DALAM SELEKSI ANGGOTA KPU DAN BAWASLU DEMI TERWUJUDNYA PRINSIP CHECK AND BALANCES - Silalahi, Jordan Baros Indraputra; Silalahi, Thomas Rifera Indraputra (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
The principle of checks and balances is a fundamental element in a democratic system to ensure a balance of power among state institutions. In the context of selecting members of the General Elections Commission (KPU) and the Election Supervisory Board (Bawaslu) in Indonesia, the House of Representatives (DPR) holds the authority to conduct fit and proper tests. This study aims to analyze the role of the DPR in the selection mechanism of KPU and Bawaslu members and to evaluate the extent to which the current mechanism functions effectively. The research method employed is normative legal research with a statutory approach and descriptive analysis of applicable regulations. The findings indicate that although the involvement of the DPR can reinforce the principle of checks and balances, the current selection process still allows room for political intervention and conflicts of interest. To address these issues, this study proposes a Reverse Selection mechanism, which involves reversing the roles between the DPR and the Selection Committee to enhance the independence, transparency, and objectivity of the KPU and Bawaslu selection process. The implementation of this mechanism is expected to improve the governance of electoral body selection in Indonesia.